2012
DOI: 10.1271/bbb.120299
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of ACE Inhibitory Tripeptides, Val-Pro-Pro and Ile-Pro-Pro, in Vascular Endothelial Cells

Abstract: The antihypertensive peptides, Val-Pro-Pro and Ile-Pro-Pro, were successfully detected in the aorta of spontaneously hypertensive rats after orally administering these peptides by a guanidine-thiocyanate treatment to prevent proteolysis. Cy3-labeled versions of both peptides were localized in the endothelial cells of arterial vessels in the rats. The accumulation of both peptides in the endothelial cells suggested in vivo inhibitory activity of the angiotensin I-converting enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Jauhiainen et al (2007) administered radio-labelled Ile-Pro-Pro to spontaneously hypertensive rats (SHR) both intravenously and orally and subsequently radioactivity was detected in aorta, heart and kidneys for as long as 48 h after their administration. Kawaguchi et al (2012) detected labelled Ile-Pro-Pro and Val-Pro-Pro in the endothelium of rats after oral administration of these compounds. They also measured Ile-Pro-Pro and Val-Pro-Pro concentrations in plasma and tissues; liver, kidneys, lung and aorta (concentrations from lowest to highest).…”
Section: Ile-pro-pro Val-pro-pro and Leu-pro-promentioning
confidence: 94%
See 2 more Smart Citations
“…Jauhiainen et al (2007) administered radio-labelled Ile-Pro-Pro to spontaneously hypertensive rats (SHR) both intravenously and orally and subsequently radioactivity was detected in aorta, heart and kidneys for as long as 48 h after their administration. Kawaguchi et al (2012) detected labelled Ile-Pro-Pro and Val-Pro-Pro in the endothelium of rats after oral administration of these compounds. They also measured Ile-Pro-Pro and Val-Pro-Pro concentrations in plasma and tissues; liver, kidneys, lung and aorta (concentrations from lowest to highest).…”
Section: Ile-pro-pro Val-pro-pro and Leu-pro-promentioning
confidence: 94%
“…Bioavailability of food-derived components, that is, their absorption from intestine to the systemic circulation is an important issue when examining the physiological effects of nutrients. Ile-Pro-Pro, Leu-Pro-Pro and Val-Pro-Pro have been detected in the circulation after oral administration of dairy products enriched with these peptides both in experimental and human studies (Jauhiainen et al, 2007;van der Pijl et al, 2008;Kawaguchi et al, 2012;Gleeson et al, 2017). The levels of the detected tripeptides are low; however, but there were some indications that there was an accumulation of peptides in blood pressure regulating organs.…”
Section: Ile-pro-pro Val-pro-pro and Leu-pro-promentioning
confidence: 99%
See 1 more Smart Citation
“…IPP and VPP have been shown to improve endothelial function in isolated SHR mesenteric arteries (Jakala, Pere et al., ; Jakala, Hakala et al., ). Cy3‐labeled both of IPP and VPP shown that both peptides existed in the endothelial cells of blood vessels in the SHRs and this accumulation could act as ACE inhibitor after oral administration (Kawaguchi, Nakamura, Kamiie, Takahashi, & Yamamoto, ). In cultured vascular endothelial cells and isolated aortic rings, IPP and VPP could stimulate the production of vasorelaxant substances (that is, NO and EDHF) through B2 receptor (Hirota et al., ).…”
Section: The Mechanism Of Tripeptides Ipp and Vppmentioning
confidence: 99%
“…Znaczną większość bioaktywnych peptydów stanowią krótkie fragmenty -di-oraz tripeptydy (np. duża część inhibitorów ACE), które mogą przekraczać barierę jelitową i docierać w postaci niezmienionej do miejsca oddziaływania, a następnie wpływać na funkcje fizjologiczne organizmu [41,96]. Wchłanianie peptydów przez jednowarstwowe komórki nabłonka jelitowego może odbywać się w różny sposób [88].…”
Section: Biodostępność Peptydów Bioaktywnychunclassified